Perceptions of Bedside Nurses Caring for Patients with Left Ventricular Assist Devices (LVAD): A Qualitative Study - Sara El Zein; Mirna Fawaz; Mohammad N. Al-Shloul; Ahmad Rayan; Mohammed S ALBashtawy; Imad Abu Khader; Mohammed Jallad; Muna Al-Kharabsheh; Sa'd ALBashtawy; Doha M. Alshloul (SAGE Publishing, 2024)
Introduction Bedside nurses in the intensive care units are exposed to multiple challenges in their regular practice and recently have taken in ventricular assist device care in Lebanon since its introduction as a fairly new practice. Objectives To explore the experiences of nursing staff who work in Lebanese hospitals with Left Ventricular Assist Devices (LVAD). Methods This study employed a qualitative phenomenological research design, where semi-structured interviews were carried out among fifteen LVAD nurses in an acute care hospital. Results The qualitative data analysis produced six main themes. The first theme prevalent was "LVAD incompetence and shortage" and it reflected the deficit in properly structured training and the number of specialized LVAD nurses. The second theme that resulted from the analysis was titled, "Patient and family knowledge", which indicated the misconceptions that families and patients usually hold about LVAD which usually sugarcoats the situation. This was followed by "Burden of complications", "LVAD patient selection", "Perception of the LVAD team as invulnerable", and "High workload and patient frailty" which reflected the perspectives of LVAD nurses. Conclusion This study shows that the Lebanese LVAD nurses who participated in this study perceived inadequate competence, yet lacked proper training and induction. The nurses reported multiple challenges relating to care tasks, workload, and patient and family interactions which need to be addressed by coordinators.